FAKTOR-FAKTOR YANG MEMPENGARUHI KONSUMEN DALAM PENGAMBILAN KEPUTUSAN PEMBELIAN SAYUR ORGANIK PADA USAHA KEDAI TANIKU - Rita Nurjannah; Yoga Nugroho (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
Kedai Taniku is a digital platform for providing horticultural agricultural products, one of which is organic vegetables. The Kedai Taniku business is a newly developed business that requires information regarding consumer factors in making purchasing decisions as well as consumers who do not buy organic vegetables at Kedai Taniku where this information can be used as a reference for developing the Kedai Taniku business. This research was conducted in West Aceh District, namely in the Kedai Taniku business. The choice of business in this study was carried outpurposivelybecause it is a digital platform for marketing agricultural products that partners in the ORMAWA BEM FP UTU service program and is a newly developed business. This research was conducted from October to November 2022. The method used in this research is the Logistic Regression method. Based on the data processing, it is obtained that variables that have a significant effect on purchasing decisions/decisions are not variables that affect purchasing decisions/decisions not to buy including Revenue (X1) with sig. 0.004, Lifestyle (X2) with sig. 0.035, Price (X3) with sig. 0.017, and Promotion (X6) with a sig. 0.020, Distribution (X7) with sig. 0.005, Quality (X8) with sig. 0.039. The variables that have no effect include the Process variables (X4) and Location (X5).